The The Effects of Entrepreneurial Behavior on Seaweed Business Performance in Takalar Regency - Siti Hardiyanti Syam; Rachmat Pambudy; Wahyu Budi Priatna (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Seaweed is one of the main aquaculture products which has high economic value and serves as strategic business opportunities. Seaweed farming becomes the main livelihood for people in Takalar Regency, so it is necessary to improve the working quality of seaweed farmers through the development of entrepreneurial behavior as a new variable in improving the performance of seaweed business. This research is intended to examine the effects of the environment on farmers’ entrepreneurial behavior and the effects of entrepreneurial behavior on seaweed business performance. This research takes place in two different production districts, which are Mangarabombang district and Mappakasunggu district, with 150 respondents of seaweed farmers conducted by simple random sampling. The data analysis method used in this research is the Structural Equation Model (SEM) using AMOS 23 software. The result shows that there are insignificant positive impacts of the internal environment on farmers’ entrepreneurial behavior as the value of t-statistic is 1.61 < 1.96, while there are significant positive impacts of the external environment on farmers’ entrepreneurial behavior with the coefficient value of 0.58 and t-statistic of 2.50. The entrepreneurial behavior is found to give significant and positive impacts towards farm performance with the coefficient value if 0.41 and t-statistic of 5.26 > 1.96. It shows that the development of farmers’ entrepreneurial behavior will improve the seaweed business performance in Takalar Regency. Keywords: entrepreneurial behavior, business performance, seaweed, structural equation model